Comparisons of benefits and risks of single embryo transfer versus double embryo transfer: a systematic review and meta-analysis - Shujuan Ma; Yangqin Peng; Liang Hu; Xiaojuan Wang; Yiquan Xiong; Yi Tang; Jing Tan; Fei Gong (BMC, 2022)
Abstract Background Evidence referring to the trade-offs between the benefits and risks of single embryo transfer (SET) versus double embryo transfer (DET) following assisted reproduction technology are insufficient, especially for those women with a defined embryo quality or advanced age. Methods A systematic review and meta-analysis was conducted according to PRISMA guidelines. PubMed, EMBASE, Cochrane Library and ClinicalTrials.gov were searched based on established search strategy from inception through February 2021. Pre-specified primary outcomes were live birth rate (LBR) and multiple pregnancy rate (MPR). Odds ratio (OR) with 95% confidence interval (CI) were pooled by a random-effects model using R version 4.1.0. Results Eighty-five studies (14 randomized controlled trials and 71 observational studies) were eligible. Compared with DET, SET decreased the probability of a live birth (OR = 0.78, 95% CI: 0.71-0.85, P < 0.001, n = 62), and lowered the rate of multiple pregnancy (0.05, 0.04-0.06, P < 0.001, n = 45). In the sub-analyses of age stratification, both the differences of LBR (0.87, 0.54-1.40, P = 0.565, n = 4) and MPR (0.34, 0.06-2.03, P = 0.236, n = 3) between SET and DET groups became insignificant in patients aged ≥40 years. No significant difference in LBR for single GQE versus two embryos of mixed quality [GQE + PQE (non-good quality embryo)] (0.99, 0.77-1.27, P = 0.915, n = 8), nor any difference of MPR in single PQE versus two PQEs (0.23, 0.04-1.49, P = 0.123, n = 6). Moreover, women who conceived through SET were associated with lower risks of poor outcomes, including cesarean section (0.64, 0.43-0.94), antepartum haemorrhage (0.35, 0.15-0.82), preterm birth (0.25, 0.21-0.30), low birth weight (0.20, 0.16-0.25), Apgar1 < 7 rate (0.12, 0.02-0.93) or neonatal intensive care unit admission (0.30, 0.14-0.66) than those following DET. Conclusions In women aged < 40 years or if any GQE is available, SET should be incorporated into clinical practice. While in the absence of GQEs, DET may be preferable. However, for elderly women aged ≥40 years, current evidence is not enough to recommend an appropriate number of embryo transfer. The findings need to be further confirmed.